Analysis of the drying behavior of suspension drops with spherical and ellipsoidal particles. Issue 16 (10th December 2018) - Park, Baek Sung; Ahn, Won-Gi; Jung, Kevin Injoe; Lee, Seong Jae; Lee, Kwan-Young; Jung, Hyun Wook
ABSTRACT: Employing multispeckle diffusing wave spectroscopy (MSDWS) as a noncontact light scattering method, drying dynamics of suspension drops with spherical and ellipsoidal particles have been investigted in real time. Scattered light intensity data during drying are converted to calculate the autocorrelation fuction and moment of inetia (IM) through co-occurrence matrix (COM). Using IM data, it is found that drying patterns of drops could be clearly divided into compacting and air-invading stages. Compared with the case with spherical particles, ellipsoidal particles with lower mobility in a suspension drop augment the period of air-invading stage in drying process due to the loosely packed pore structures between particles.